PyMED-DX: A Python tool for diagnostic value evaluation of 2D medical images - Gorana Gojić; Vladimir Vincan; Ognjen Kundačina; Saša Taloši; Dragiša Mišković (SoftwareX)
This paper presents a Python-based tool designed to simplify subjective assessment studies for diagnostic value assessment of 2D medical images. The tool facilitates rapid questionnaire generation, allowing users to integrate their data into predefined templates, and provides utilities to statistically and visually analyze collected responses. By reducing the technical overhead of study preparation, the tool allows users to focus on knowledge discovery while providing easy-to-use questionnaires for clinicians with no technical expertise required.